Desarrollo de un Simulador Parametrizable de 5G-New Radio basado en Ray Tracing para Planificación de Celdas Urbanas - Bryan Sanipatin; Jefferson Ribadeneira (NOVASINERGIA, 2023)
Nowadays, the 5G New Radio broadband technology has begun to be deployed. Therefore, new tools focused on studying the standard and propagation conditions are needed. In this context, the development of a 5G New Radio simulator that allows experimentationwith the different signal parameters, as well as to identify the main characteristics at the link level and wave propagation, is presented. The essential parts of the standard were analyzed and introduced into the software, from which the Physical DownlinkShared Channel and the Physical Uplink Shared Channel could be parametrized. Regarding urban cell planning, two calculations are included: i) SINR maps that allow the visualization of Signal to Noise and Interference Ratio (SINR) for parametrizable numbers of gNodeB, transmission power, downtilt, and so on;ii) Coverage simulation based on ray-tracing in 3D maps that also considerthe permittivityand conductivity of buildings and terrain materials. Additionally, for channel characterization, the simulatorpresents the Power Delay Profile (PDP), and if there is movement, the Doppler shift is represented in the Scattering function. The result is a parameterizable simulator that integrates 5G-NR signal generation and coverage calculations for the deployment of 5G urban cells, with an average difference inthe ray-tracing case of 7.11 dB between the measured and calculated values.